2021
DOI: 10.1186/s12870-021-02843-8
|View full text |Cite
|
Sign up to set email alerts
|

Screening the elite chemotypes of Gloriosa superba L. in India for the production of anticancer colchicine: simultaneous microwave-assisted extraction and HPTLC studies

Abstract: Background Gloriosa superba L. (Colchicaceae) is a high-value medicinal plant indigenous to Africa and Southeast Asia. Its therapeutic benefits are well-established in traditional medicines including Ayurveda. It is well known for its natural bioactive compound colchicine which exhibits a wide range of pharmacological activities i.e. rheumatism, gout and was also introduced into clinical practices. The increasing demand as well as its illegal harvesting has brought this valuable plant under thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 53 publications
(57 reference statements)
0
12
0
Order By: Relevance
“…For its determination in serum and plasma samples, various liquid chromatography-mass spectrometry (LC-MS) methods have been reported [1,[22][23][24]. For the determination of this compound in various commercial formulations and plant extracts, distinct high-performance thin-layer chromatography (HPTLC) assays have been reported [10,[25][26][27][28][29][30][31][32][33][34][35]. Some electrochemical techniques have also been utilized for the determination of this compound [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…For its determination in serum and plasma samples, various liquid chromatography-mass spectrometry (LC-MS) methods have been reported [1,[22][23][24]. For the determination of this compound in various commercial formulations and plant extracts, distinct high-performance thin-layer chromatography (HPTLC) assays have been reported [10,[25][26][27][28][29][30][31][32][33][34][35]. Some electrochemical techniques have also been utilized for the determination of this compound [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…Being a mycorrhizal plant, association with arbuscular mycorrhizal (AM) fungi would aid G. superba in its growth and secondary metabolite production. For instance, Pandey et al (2021) showed that inoculation of AM fungi along with or without phosphorous fertilizer supplementation increased colchicine content in the tubers of G. superba . In addition to AM fungi, the roots of G. superba are also colonized by the ascomycetous dark septate endophytic (DSE) fungi (Muthukumar et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…It is categorized as endangered by International Union for Conservation of Nature (IUCN) in India due to overexploitation of the species for various medicinal purposes (Tilwari & Sharma, 2021; Yadav et al, 2012). Colchicine is one of the important alkaloids present in G. superba that helps in treating various human ailments (Balkrishna et al, 2019; Pandey et al, 2021). Therefore, it is important to conserve this plant in its natural habitats for the future.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As plants proceed through their normal metabolic processes, they form phytochemicals. The term "secondary metabolites" refers to the many kinds of chemicals which can be found in plants, namely alkaloids, coumarins, flavonoids, glycosides, gums, phenols, polysaccharides, tannins, terpenes, and terpenoids [80,126]. Plants also contain other chemical compounds in addition to these.…”
Section: Introductionmentioning
confidence: 99%